The Role of Ikhwanul Muslimin in Egypt’s Political Dynamics Post-Arab Spring: An Analysis through David Easton’s Political System Framework - WIYANA, Rachmat Indra (Journal of Political And Legal Sovereignty, 2024)
Purpose:This study analyzes the influence of Ikhwanul Muslimin on Egypt’s political dynamics after the Arab Spring, using David Easton’s political system framework. The Arab Spring, which began in late 2010, ignited widespread revolutions across Arab nations, including Egypt, with aspirations for more democratic governance. Ikhwanul Muslimin emerged victorious in Egypt’s 2012 elections, with Mohamed Morsi becoming president. However, the movement faced significant setbacks after the 2013 military coup led by General Abdel Fattah el-Sisi, which resulted in widespread repression and arrests of its members.Methodology:This research employs a qualitative descriptive approach and case study method to explore the role and influence of Ikhwanul Muslimin in Egypt's political processes and the challenges they faced in this context.Findings:The study reveals that government policies towards Ikhwanul Muslimin have significantly impacted Egypt's political stability, human rights, and civil liberties. It sheds light on the broader challenges faced by Islamist movements in navigating modern political systems.Implication:The findings provide critical insights into the dynamics of Islamist movements within transitional political contexts, offering valuable perspectives on their role, limitations, and the broader implications for political stability and governance in the Middle East.